The Effect Of Customer Service, Interest Rate Level And Guaranteed Sense Of Security On Customer Saving Interest At Bank Ntt Kcu Kota Kupang - Klau, Reinaldus Yohanes D; Kiak, Novi Theresia; Tungga, Cicilia A (Universitas Dharmawangsa Medan, 2025)
This research aims to analyze the influence of customer service, interest rates, and security guarantees on customers' interest in savings at Bank NTT Main Branch Office (KCU) Kupang City. This study uses a quantitative method with a descriptive approach. Data collection was carried out through the distribution of questionnaires to Bank NTT customers and data analysis using multiple linear regression. The results of the study show that customer service has a positive and significant effect on saving interest. Interest rates also have a significant influence, this shows that the higher the interest offered, the greater the interest of customers to save. In addition, the security guarantees provided by banks make a positive contribution to the customer's decision to keep their funds. Simultaneously, the three independent variables (customer service, interest rates, and security guarantees) have a significant influence on the bound variable (interest savings). The results of this study provide important implications for the management of Bank NTT to continue to improve the quality of services, provide competitive interest rates, and ensure security and trust in banking transactions. This research is expected to be an input for Bank NTT in improving service quality, providing competitive interest rates, and providing a sense of security and trust in banking transactions.